PENGARUH AROMATERAPI KAYU MANIS TERHADAP NYERI HAID PRIMER PADA REMAJA DI DESA PASIR GADUNG TANGERANG - Friesca Berlianie Poetri; Selvy Afrioza; Rina Puspitasari (Universitas Muhamadiyah Manado, 2022)
Menstrual pain caused by the release of excess prostaglandin causes the increasing contraction of the uterus, a common gynecology disorder in young women that can interfere with learning and social activity. Based on a preliminary study in the village of the gadung young women take pharmacological medicines and warm compresses to hold or reduce menstrual pain. The study to learn the aromatherapy of cinnamon on primary menstrual pain in young women in the village of gadung tangerang. This method of research USES quantitative with research design quasi nity, one group pre-existing and post-existing. The study conducted according to the inclusion and exclusion criteria amounts to 38 respondents and instrument of the observation sheet. That was done with Shapiro wilk and a statistic wilcoxon signed rank. Studies show 7 days of cinnamon aromatherapy intervention, a scale of pain reduced from 1.79 to 1. Wilcoxon signed rank test results of a significant influence between the scale of pain before and after an intervention on cinnamon aroma recipients in the village of gadung sand. Aroma of cinnamon therapy may be an alternative to reduce menstrual pain.